Genetic dissection of sex determinism, inflorescence morphology and downy mildew resistance in grapevine - Marguerit, Elisa; Boury, Christophe; Manicki, Aurélie; Donnart, Martine; Butterlin, Gisèle; Némorin, Alice; Wiedemann-Merdinoglu, Sabine; Merdinoglu, Didier; Ollat, Nathalie; Decroocq, Stéphane (Theoretical and applied genetics, 2009)
A genetic linkage map of grapevine was constructed using a pseudo-testcross strategy based upon 138 individuals derived from a cross of Vitis vinifera Cabernet Sauvignon x Vitis riparia Gloire de Montpellier. A total of 212 DNA markers including 199 single sequence repeats (SSRs), 11 single strand conformation polymorphisms (SSCPs) and two morphological markers were mapped onto 19 linkage groups (LG) which covered 1,249 cM with an average of 6.7 cM between markers. The position of SSR loci in the maps presented here is consistent with the genome sequence. Quantitative traits loci (QTLs) for several traits of inflorescence and flower morphology, and downy mildew resistance were investigated. Two novel QTLs for downy mildew resistance were mapped on linkage groups 9 and 12, they explain 26.0-34.4 and 28.9-31.5% of total variance, respectively. QTLs for inflorescence morphology with a large effect (14-70% of total variance explained) were detected close to the Sex locus on LG 2. The gene of the enzyme 1-aminocyclopropane-1-carboxylic acid synthase, involved in melon male organ development and located in the confidence interval of all QTLs detected on the LG 2, could be considered as a putative candidate gene for the control of sexual traits in grapevine. Co-localisations were found between four QTLs, detected on linkage groups 1, 14, 17 and 18, and the position of the floral organ development genes GIBBERELLIN INSENSITIVE1, FRUITFULL, LEAFY and AGAMOUS. Our results demonstrate that the sex determinism locus also determines both flower and inflorescence morphological traits.